A Blinded Randomized Trial Comparing 2 Needle Gauges for Fine-Needle Biopsy of Thyroid Nodules. Issue 2 (May 2021) - Shumrick, Christopher M.; Simmonds, Jonathan C.; Ogden, Lorna L.; Snowden, Cindi A.; Dhingra, Jagdish K.
Objective: To compare diagnostic capability and patient pain between 25-gauge (25G) and 27G needles for ultrasound-guided fine-needle biopsy of thyroid nodules. Study Design: Prospective blinded randomized trial. Setting: Thyroid clinic in otolaryngology practice in a community. Methods: A prospective randomized blinded trial was conducted on 148 thyroid nodules in 107 patients undergoing ultrasound-guided fine-needle biopsy. Needle gauge was randomized to individual nodule. Patients were blinded to the needle size used. All specimens were assessed via the Bethesda System for Reporting Thyroid Cytopathology and assigned a morphologic quantitative score based on number of thyroid cells and lymphocytes, amount of colloid, and degree of blood/fibrin artifact in each sample. Patient pain experience was scored. A chi-square test was used to compare nondiagnostic rates, and differences in cytologic morphology and pain scores were compared with 2-sample Student t tests. Results: Of the 148 nodules, 77 were biopsied with 25G needles and 71 with 27G needles. Twenty-five percent (19/77) of the samples obtained with 25G needles yielded a nondiagnostic cytology result (Bethesda category 1) as compared with 11% (8/70) in the 27G group ( P = .0282; 95% CI, 1.47%-25.97%). On average, samples from 25G needles had a higher blood/fibrin quantitative score ( P = .043; 95% CI, −0.64 to −0.010). There were no differences in pain between groups. Conclusion: Use of a 27G needle for fine-needle biopsies is not only safe and feasible but desirable and highly recommended, as it yields better diagnostic information.